Effects of testosterone on lipid peroxidation, lipid profiles and some coagulation parameters in rabbits - Aydilek, N.; Aksakal, M. (My University, 2005)
The purpose of this study was to investigate the effects of testosterone on some risk factors of atherosclerosis. Twenty-four male New Zealand white rabbits were randomly divided into three groups of eight. The first group was used as control. Second group was injected with 10 mg of testosterone propionate. Third group was castrated bilaterally. At the end of 6 weeks, lipid peroxidation (LPO), lipid profile, fibrinogen (FBN) level and coagulation parameters were evaluated. Testosterone administration decreased the level of high-density lipoprotein cholesterol (HDL-C), while castration increased this level (P < 0.05). Triglyceride (TG) and total cholesterol (TC) levels in the castration group were significantly higher (P < 0.05) than those in the testosterone group. The ratio of HDL-C:low-density lipoprotein cholesterol (LDL-C) decreased, while TC:HDL-C ratio increased (P < 0.05) in the testosterone group. No significant differences were found in the LDL-C and FBN levels among groups. However, there was a tendency for higher FBN level in the testosterone group. Testosterone administration resulted in an increase in the level of LPO (P < 0.05). Clotting time and prothrombin time prolonged in the castration group compared with testosterone group (P < 0.05). As a result, testosterone has exacerbating effect on atherosclerosis risk factors including lipid profile, LPO, FBN and coagulation system. © 2005 Blackwell Verlag.
Keywords: Animals; Blood Coagulation; Cholesterol; Fibrinogen; Lipid Peroxidation; Lipids; Male; Orchiectomy; Rabbits; Random Allocation; Testosterone; Triglycerides; Oryctolagus cuniculus; cholesterol; fibrinogen; lipid; testosterone; triacylglycerol; animal; animal disease; article; blood; blood clotting; drug effect; lipid peroxidation; male; orchiectomy; rabbit; randomization